Hot and Cold Pressed LGPS Solid Electrolytes. Issue 1 (22nd January 2021) - Wang, Yang; Hoang, Binh; Hoerauf, John; Lee, Cholho; Lin, Chuan-Fu; Rubloff, Gary W.; Lee, Sang Bok; Kozen, Alexander C.
Abstract : Li10 GeP2 S12 (LGPS) is a superionic conductor that has an ionic conductivity matching conventional liquid electrolytes (10 −3 S cm −1 ) and thus shows exceptional potential to fulfill the promise of solid-state Li metal batteries. Conventional mechanical die pressing of LGPS powder into pellets for electrochemical testing can result in large porosity, low density, and large grain boundary resistance at the solid-solid interface with the electrodes which greatly decrease the performance of LGPS, in addition to poor mechanical stability of such pressed pellets. We demonstrate the use of hot pressing to fabricate of LGPS pellets using commercially available powder. We obtain pellets that are the most dense, and accordingly have the highest ionic conductance, at 150 °C. XPS demonstrates there is no chemical degradation of the LGPS powder during the hot pressing process.